2007
DOI: 10.1152/ajprenal.00088.2007
|View full text |Cite
|
Sign up to set email alerts
|

Proinflammatory and proliferative responses of human proximal tubule cells to PAR-2 activation

Abstract: Despite the abundant expression of protease-activated receptor (PAR)-2 in the kidney, its relevance to renal physiology is not well understood. A role for this receptor in inflammation and cell proliferation has recently been suggested in nonrenal tissues. The aims of this study were to demonstrate that human proximal tubule cells (PTC) express functional PAR-2 and to investigate whether its activation can mediate proinflammatory and proliferative responses in these cells. Primary human PTC were cultured under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
31
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 37 publications
1
31
0
Order By: Relevance
“…Phosphorylated Smad2/3 forms an oligomeric complex with Smad4, which then translocates to the nucleus to initiate the transcription of genes that regulate fibrosis, cell proliferation, differentiation, and apoptosis (42). Previous observations in isolated cultured human tubular epithelial cells have demonstrated that functional epithelial PAR2 activation stimulates the production of monocyte chemotactic protein-1 and TGF␤ (11). In addition to a proinflammatory role of PAR2, our data shows that PAR2 contributes to profibrotic pathways by acting synergistically with TGF␤ to induce Smad2 activation and CTGF expression consistent with the in vivo studies.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Phosphorylated Smad2/3 forms an oligomeric complex with Smad4, which then translocates to the nucleus to initiate the transcription of genes that regulate fibrosis, cell proliferation, differentiation, and apoptosis (42). Previous observations in isolated cultured human tubular epithelial cells have demonstrated that functional epithelial PAR2 activation stimulates the production of monocyte chemotactic protein-1 and TGF␤ (11). In addition to a proinflammatory role of PAR2, our data shows that PAR2 contributes to profibrotic pathways by acting synergistically with TGF␤ to induce Smad2 activation and CTGF expression consistent with the in vivo studies.…”
Section: Discussionsupporting
confidence: 90%
“…In the kidney, PAR2 is abundantly expressed in the proximal tubular cells of renal cortex, and renal PAR2 activation is associated with changes in renal hemodynamics, ion secretion, and inflammation (9,10). Studies have also indicated a proinflammatory role for PAR2 in the kidney, as receptor stimulation with PAR2-AP was found to augment MCP-1 production in human proximal tubular cell cultures (11).…”
mentioning
confidence: 99%
“…That Endogenously Express PAR2-In order to confirm the existence of NE-dependent biased signaling in cells that endogenously express PAR2, we have examined the effect of NE on calcium and MAPK signaling in HPT cells that naturally express high levels of PAR2 (24). Treatment of HPT cells with NE did not stimulate a calcium signal but significantly attenuated subsequent trypsin-stimulated calcium transients (Fig.…”
Section: Ne Disarms Calcium Signaling and Activated Mapk Signaling Inmentioning
confidence: 97%
“…Within the human kidney, PAR2 is especially prominent in the proximal tubule cells of the renal cortex and renal vasculature (21,48,49). Studies have shown PAR2 involvement in the control of renal blood flow, ion transport, inflammation, and fibrosis (5,17,18,21).…”
mentioning
confidence: 99%